Thermal conductivity, structure and mechanical properties of konjac glucomannan/starch based aerogel strengthened by wheat straw. (1st October 2018) - Wang, Yixin; Wu, Kao; Xiao, Man; Riffat, Saffa B.; Su, Yuehong; Jiang, Fatang
Highlights: Four natural raw materials were used for KGM/starch based aerogel preparation. KGM/starch based aerogel preparation via an energy efficient freeze drying method. Starch was used to increase the mechanical strength of KGM/starch based aerogels. Wheat straw can improve thermal insulation by affecting pore structure. Thermal insulation mechanism of KGM/starch based aerogel was discussed. Abstract: This study presents the preparation and property characterization of a konjac glucomannan (KGM)/starch based aerogel as a thermal insulation material. Wheat straw powders (a kind of agricultural waste) and starch are used to enhance aerogel physical properties such as mechanical strength and pore size distribution. Aerogel samples were made using environmentally friendly sol–gel and freeze drying methods. Results show that starch addition could strengthen the mechanical strength of aerogel significantly, and wheat straw addition could decrease aerogel pore size due to its special micron-cavity structure, with appropriate gelatin addition as the stabilizer. The aerogel formula was optimized to achieve lowest thermal conductivity and good thermal stability. Within the experimental range, aerogel with the optimized formula had a thermal conductivity 0.04641 Wm −1  K −1, a compression modulus 67.5 kPa and an elasticity 0.27. The results demonstrate the high potential of KGM/starch based aerogels enhanced with wheat straw for application in thermal insulation.